Diversity-Oriented Synthesis via Catalyst-Free Addition of Ketones to [e]-Fused 1H-Pyrrole-2,3-diones - Stepanova, Ekaterina E.; Kasatkina, Svetlana O.; Dmitriev, Maksim V.; Maslivets, Andrey N. (Synthesis, 2018)
A facile synthetic approach towards two distinct pyrrole-based heterocyclic scaffolds has been developed by the interaction of 1H-pyrrole-2,3-diones fused at the [e]-side to a 1,4-benzoxazin-2-one or quinoxalin-2(1H)-one moiety with ketones. The described interaction proceeds either as an aldol reaction or as a Michael addition/intramolecular cyclization depending on the reaction conditions. The disclosed aldol reaction proceeds with good diastereoselectivity under catalyst-free conditions when the reaction is carried out in aromatic hydrocarbons. Products of the cascade Michael addition/intramolecular cyclization reaction are predominantly formed under catalyst-free and solvent-free conditions. The proposed strategy provides facile access to pharmaceutically interesting pyrrole-based polyheterocycles.
Keywords: aldol reaction; fused-ring systems; Michael addition; nitrogen heterocycles; polycycles